(3GdfhGOQ GdSdWGfjI hGdeMGSf GdjhSajgs - (3GHf TOGO , jhSa Hf QGaY Hf Jeje Hf YJHg GdCSOj GdehUdj, HgGA GdOjf CHh GdeMGSf,J (B632 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HGdESdGe s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B299s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B328 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs